2008
DOI: 10.1002/jsfa.3328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant cultivation methods on content of major and trace elements in foodstuffs and retention in rats

Abstract: BACKGROUND: Many consumers perceive organic foods as more nutritious than conventional foods. However, the existing evidence is insufficient to support or refute this belief. The purpose of the present study was to investigate the effect of three different model cultivation systems on selected major and trace element contents of dried foodstuffs (carrots, kale, peas, potatoes and apples) grown in two consecutive years, as well as mineral retention determined in 36 rats (second generation in a multi-generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…The difference in protein content observed on the freeze‐dried carrots was, however, eliminated in the complete carrot‐based diets, due to the diluting effect of the 60% Altromin and overall no effect of cultivation system was observed on the chemical composition of the carrot‐based diets. Moreover the digestibility was also unaffected by cultivation system, which is in accordance with a previous rat study on organic versus conventional food where little difference between cultivation systems on mineral32 and protein and energy21 digestibility was shown. However, DM digestibility was higher for carrot‐based diets than for CO.…”
Section: Discussionsupporting
confidence: 91%
“…The difference in protein content observed on the freeze‐dried carrots was, however, eliminated in the complete carrot‐based diets, due to the diluting effect of the 60% Altromin and overall no effect of cultivation system was observed on the chemical composition of the carrot‐based diets. Moreover the digestibility was also unaffected by cultivation system, which is in accordance with a previous rat study on organic versus conventional food where little difference between cultivation systems on mineral32 and protein and energy21 digestibility was shown. However, DM digestibility was higher for carrot‐based diets than for CO.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the differences in carotenoid content between the organic and non-organic baby foods reflect the types of ingredients incorporated into these meals. Overall, our data suggest that organic baby foods are not superior to non-organic baby meals, which is in agreement with Kristensen et al (2008), who concluded that, in general, organically grown foodstuffs do not have greater nutritional value than conventionally grown foods. Garrett et al (1999a) developed an in vitro digestion model to estimate the relative bioavailability of carotenoids from a baby meal that was prepared in a way representative of a typical meal for infants, i.e.…”
Section: Carotenoid Content In Organic Vs Non-organic Baby Foodssupporting
confidence: 93%
“…In fact, Catania Plain soil had high levels of Na and Mg (Table 1), while the soil of Gela Plain showed a high level of K, similarly found in globe artichoke planted there. This might have also affected the Mg level in Gela Plain, since high levels of K decrease the amount of Mg absorbed by plants 28. The higher cation exchange capacity and electrical conductivity, recorded in soil of Gela Plain (Table 1), also influenced the Na and Fe levels in globe artichoke capitula.…”
Section: Resultsmentioning
confidence: 97%